AN AUDIT OF OXYGEN PRESCRIBING PRACTICES IN RESPIRATORY WARDS OF A TERTIARY CARE HOSPITAL IN NOTTINGHAMSHIRE, UK - Ahmed, Hassan; Nataraju, Kruthika; Elmahdy, Ahmed A; Cheema, Muhammad Afrasiyab (Journal of Ayub Medical College Abbottabad, 2024)
Background: This audit primarily assesses compliance with the British Thoracic Society guidelines (BTS) for oxygen prescriptions in the Respiratory Department at King’s Mill Hospital. The results of this audit aim to guide the strategies to improve the oxygen prescription practices in the Trust. Methods: We collected the data on oxygen prescriptions, from the electronic prescribing system, of all the patients admitted in the three respiratory wards of King’s Mill Hospital over the period of one week. This data was then recorded and analysed using Audit management and Tracking© (AMAT). Results: The overall compliance score to BTS guidelines for oxygen prescription was 12.2%. Out of the 152 patients, only 8 (5%) had oxygen therapy prescribed and a target oxygen saturation range was identified. No patient had an identifiable oxygen delivery method on their prescription. Conclusion: The current practices of oxygen prescription at the respiratory department of King’s Mill Hospital are suboptimal. These findings highlight the risk of serious potential consequences and the opportunity to implement safe prescribing measures for oxygen, like other prescribed medications.